Theory of antiferromagnetic pairing in cuprate superconductors: Spin Models - Plakida, N.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
A review of the antiferromagnetic exchange and spin-fluctuation pairing theory in the cupratesuperconductors is given. We briefly discuss a phenomenological approach and a theory in the limit of weak Coulomb correlations. A microscopic theory in the strong correlation limit is presented in more detail. In particular, results of our recently developed theory for the effective p–d Hubbard model and the reduced t–J model are given. We have proved that retardation effects for the antiferromagnetic exchange interaction are unimportant that results in pairing of all charge carriers in the conduction band and high Tc proportional to the Fermi energy. The spin-fluctuation interaction caused by kinematic interaction gives an additional contribution to the d-wave pairing. Dependence of Tc on the hole concentration and the lattice constant (or pressure) and an oxygenisotope shift are discussed.